Recognition of electronic bill of lading in commercial transactions: A critical study of the Legal framework in Tanzania - Matovu, Ebbychris (Mzumbe Unversity, 2024)
A dissertation submitted in partial fulfilment of the requirement for the award of Master of Laws (LL.M) Commercial Law of Mzumbe University